LINGUOCULTURAL ANALYSIS OF THE CONCEPT OF “SHAXS” IN UZBEK LINGUOCULTURE - Burieva Nilufar Gofur kizi (Bright Mind Publishing, 2025)
This study examines the linguocultural concept of “Shaxs” (person) within the Uzbek language and cultural context. Drawing on linguistic and cultural analysis, it reveals that this term embodies not only individual identity, but also moral, social, and ethical values valued in Uzbek society. The concept of “Shaxs” links personal dignity, izzat (honor) and hurmat (respect) with collective responsibility, reflecting a balance between individuality and collectivism. By examining semantic domains, idiomatic expressions, and sociolinguistic practices, the study sheds light on how Uzbek linguistic culture shapes and conveys worldviews related to the individual and social roles. This study contributes to a deeper understanding of Uzbek cultural identity and provides insight into the complex relationships between language, culture, and cognition.
Keywords: Person, Uzbek linguoculture, analysis, identity, cultural linguistics, concept.